Spatial and temporal response of wildlife to recreational activities in the San Francisco Bay ecoregion. (March 2017) - Reilly, M.L.; Tobler, M.W.; Sonderegger, D.L.; Beier, P.
Abstract: Non-motorized human recreation may displace animals from otherwise suitable habitat; in addition, animals may alter their activity patterns to reduce (or increase) interactions with recreationists. We investigated how hiking, mountain biking, equestrians, and recreationists with domestic dogs affected habitat use and diel activity patterns of ten species of medium and large-sized mammals in the San Francisco Bay ecoregion. We used camera traps to quantify habitat use and activity patterns of wild mammals and human recreationists at 241 locations in 87 protected areas. We modeled habitat use with a multi-species occupancy model. Species habitat use was most closely associated with environmental covariates such as landcover, precipitation, and elevation. Although recreation had less influence on habitat use, the presence of domestic dogs was negatively associated with habitat use of mountain lions and Virginia opossum. We also compared diel activity patterns of species at sites with no observed recreation to the activity patterns of species at sites with high (≥ eight per day) levels of non-motorized recreation. Coyotes were more active at night and less active during the day in areas with high levels of recreation. Striped skunks were slightly more active later into the morning in areas that allowed human recreation. Smaller carnivores with nocturnal activity patterns may not be directly affected by recreational activities that are limited to daylight hours. We suggest that by maintaining habitat free of domestic dogs, and creating trail-free buffers, land managers can manage recreation in a way that minimizes impacts to wildlife habitat and preserves the value of protected areas to people and wildlife.